Proceedings of the CoNLL 2020 Shared Task: Cross-Framework Meaning Representation Parsing 2020
DOI: 10.18653/v1/2020.conll-shared.1
|View full text |Cite
|
Sign up to set email alerts
|

MRP 2020: The Second Shared Task on Cross-Framework and Cross-Lingual Meaning Representation Parsing

Abstract: The 2020 Shared Task at the Conference for Computational Language Learning (CoNLL) was devoted to Meaning Representation Parsing (MRP) across frameworks and languages. Extending a similar setup from the previous year, five distinct approaches to the representation of sentence meaning in the form of directed graphs were represented in the English training and evaluation data for the task, packaged in a uniform graph abstraction and serialization; for four of these representation frameworks, additional training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 66 publications
1
35
0
Order By: Relevance
“…In this sense, we continue the recent cross-framework trend formally started by the shared task of Oepen et al (2019), exploring the possibility of using translation-based approaches for framework-independent parsing, as opposed to the transition-based parsers proposed in that seminal work. Our findings are in line with the recent results reported by Oepen et al (2020) and, in particular, by Ozaki et al (2020) (d) UCCA Linearization Figure 1: AMR and UCCA graphs, along with their linearizations, for the sentence "After graduation, John moved to Paris". To ease readability, linearizations are shown with newlines and indentation; however, when fed to the neural model, they are in a single-line single-space format.…”
Section: Related Worksupporting
confidence: 92%
See 2 more Smart Citations
“…In this sense, we continue the recent cross-framework trend formally started by the shared task of Oepen et al (2019), exploring the possibility of using translation-based approaches for framework-independent parsing, as opposed to the transition-based parsers proposed in that seminal work. Our findings are in line with the recent results reported by Oepen et al (2020) and, in particular, by Ozaki et al (2020) (d) UCCA Linearization Figure 1: AMR and UCCA graphs, along with their linearizations, for the sentence "After graduation, John moved to Paris". To ease readability, linearizations are shown with newlines and indentation; however, when fed to the neural model, they are in a single-line single-space format.…”
Section: Related Worksupporting
confidence: 92%
“…First of all, we note the result of Cross st ; while its performance is far below the score Che et al (2019) achieve, it still outperforms the original proposed baseline by more than 10 points. Furthermore, to the best of our knowledge, apart from the recent works proposed in the latest shared task of Oepen et al (2020), this is the first reported result of translation-based approaches on UCCA parsing.…”
Section: Ucca Parsingmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, most state-of-the-art work in dependency parsing uses a graph-based approach, where the assumption that the output must form a tree is only used in the final step from predicted links to final output. And finally, work on deep-syntax and semantic parsing has shown that accurate mapping of strings into rich graph representations is possible (Oepen et al, 2014(Oepen et al, , 2015(Oepen et al, , 2019(Oepen et al, , 2020 and could even lead to state-of-the-art performance for downstream applications as shown by the results of the Extrinsic Parsing Evaluation shared task (Oepen et al, 2017).…”
Section: Motivationmentioning
confidence: 99%
“…Universal Conceptual Cognitive Annotation (UCCA; Abend and Rappoport, 2013), a typologically-motivated meaning representation framework, has been targeted by several parsing shared tasks (Hershcovich et al, 2019b;Oepen et al, 2019Oepen et al, , 2020. It uses directed acyclic graphs (DAG) anchored in surface tokens, where labelled edges represent semantic relations.…”
Section: Revisiting Implicit Argument Refinementmentioning
confidence: 99%